1983
DOI: 10.1139/v83-452
|View full text |Cite
|
Sign up to set email alerts
|

Glycosides from Muscaricomosum. 4. Structure of muscaroside A

Abstract: The less polar component of the glycoside mixture extracted from the bulbs of Muscaricomosum has been completely characterized. This glycoside, 5, possesses an α-L-rhamnopyranosyl(1→2)-β-D-glucopyranosyl(1→2)-α-L-arabinopyranosyl(1→6)-β-D-glucopyranosyl chain linked at the C-3 position of eucosterol 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In connection with our studies (1)(2)(3)(4)(5) on the glycoside fraction of Muscari comosum we recently reported the isolation and structure determination of muscarosides A (4) and B (5). In this paper we describe the structure elucidation of a minor glycoside, muscaroside C, 1, which possesses a P-D-apio-Dfuranosyl( 142)-P-D-glucopyranosyl-(1-2)-a-L-arabinopyranosyl(l+6)-P-D-glucopyranosyl chain linked at the 3-position of (23S)-17,23-epoxy-3~,30,31-trihydroxy-27-nor5a-lanost-8-ene 2 (2).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In connection with our studies (1)(2)(3)(4)(5) on the glycoside fraction of Muscari comosum we recently reported the isolation and structure determination of muscarosides A (4) and B (5). In this paper we describe the structure elucidation of a minor glycoside, muscaroside C, 1, which possesses a P-D-apio-Dfuranosyl( 142)-P-D-glucopyranosyl-(1-2)-a-L-arabinopyranosyl(l+6)-P-D-glucopyranosyl chain linked at the 3-position of (23S)-17,23-epoxy-3~,30,31-trihydroxy-27-nor5a-lanost-8-ene 2 (2).…”
supporting
confidence: 70%
“…No direct evidence for the a-configuration of the L-arabinopyranosyl unit was found, owing to its high conformational mobility (4,5,17). However, an a-configuration was inferred from the striking similarity between the I " data of the L-arabinopyranosyl unit of 1 and those found for the a-L-arabinopyranosyl residues identically located in muscarosides A and B (4, 5).…”
mentioning
confidence: 96%
“…This safely established that one branch of the chain consisted of two, and only two, arabinopyranose units. (27); B, methyl a-L-arabinopyranoside (27); C, methyl a-L-rhamnopyranoside (27); D, methyl a-L-arabinofuranoside (13); E, eucosterol (4).…”
Section: Chainmentioning
confidence: 99%
“…Indeed, Parrilli et al [35] reported that the bulb of L. comosa is an important source of triterpene and glycoside, of which eucosterol 4a, a terpene of the nor-27 lanostane family, is the major compound. e same team was able to characterize the structure of glycosides from L. comosa [36]. In 1984, Adinolfi et al were able to determine the structure of new triterpenes from L. comosa bulbs harvested in Italy [37,38].…”
Section: Yields Of Aqueous and Organic Extractions Of Leopoldia Comosa (L) Bulbsmentioning
confidence: 99%